2018
DOI: 10.1111/lcrp.12147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Japanese online and standard administrations of the Gudjonsson Suggestibility Scale 2 and effects of post‐warning

Abstract: Purpose This study aimed to develop the Japanese online version of the Gudjonsson Suggestibility Scale 2 (GSS2). The effects of post‐warning and free recall on suggestibility were also examined. Methods A total of 442 people aged between 20 and 59 years took the Japanese online version of the GSS2, and their scores were compared with those obtained via administration of the Japanese standard version in a previous study and those of the British normative sample. The influence of post‐warning (a technique in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Furthermore, consistent with previous studies, Yield 2 and Shift were highly correlated, whereas Yield 1 and Shift correlated moderately. The Yield 1, Yield 2, Shift, and total suggestibility scores of the GSS 1 in the present study were significantly lower compared to previous studies on the GSS 1 (Gudjonsson, 1997;Reutemann, 2006;vom Schemm et al, 2006;Gubi-Kelm and Schmidt, 2018;Wachi et al, 2019). As Gorassini et al (2006) found similarly low Yield scores in their English online GSS 1, this discrepancy might be attributed to the online format.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Furthermore, consistent with previous studies, Yield 2 and Shift were highly correlated, whereas Yield 1 and Shift correlated moderately. The Yield 1, Yield 2, Shift, and total suggestibility scores of the GSS 1 in the present study were significantly lower compared to previous studies on the GSS 1 (Gudjonsson, 1997;Reutemann, 2006;vom Schemm et al, 2006;Gubi-Kelm and Schmidt, 2018;Wachi et al, 2019). As Gorassini et al (2006) found similarly low Yield scores in their English online GSS 1, this discrepancy might be attributed to the online format.…”
Section: Discussioncontrasting
confidence: 80%
“…Furthermore, we investigated factorial validity, configural, metric, and scalar invariance across gender and research institutions by means of multiple-group CFAs. Reliability measures were found to be comparable to faceto-face versions of the GSS 1 (Gudjonsson, 1984;Gubi-Kelm and Schmidt, 2018), but no reliability data were reported in previous online GSS studies (Gorassini et al, 2006;Wachi et al, 2019). When based on factor scores, the reliability of Yield 1 increases but is still questionable, whereas the reliabilities of Yield 2 and Shift are acceptable (George and Mallery, 2003).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations